2008
DOI: 10.1080/15228940802142852
|View full text |Cite
|
Sign up to set email alerts
|

Fenugreek (Trigonella foenum-graecumL. Leguminosae): An Evidence-Based Systematic Review by the Natural Standard Research Collaboration

Abstract: An evidence-based systematic review including written and statistical analysis of scientific literature, expert opinion, folkloric precedent, history, pharmacology, kinetics/dynamics, interactions, adverse effects, toxicology and dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 69 publications
1
47
0
Order By: Relevance
“…26 Thirty-one SRs concluded that the HM in question was safe. [13][14][15][16][17][18][19][20][21][23][24][25][26]29,31,32,35,38,39,[42][43][44][45]47,50,53,55,[57][58][59][60] Fifteen SRs reported moderately severe AEs, 12,22,27,28,30,36,40,41,46,48,49,51,52,54,56 and four SRs concluded that the HM in question was not safe (see Supplemental Tables S1 and S2). 33,34,37,…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…26 Thirty-one SRs concluded that the HM in question was safe. [13][14][15][16][17][18][19][20][21][23][24][25][26]29,31,32,35,38,39,[42][43][44][45]47,50,53,55,[57][58][59][60] Fifteen SRs reported moderately severe AEs, 12,22,27,28,30,36,40,41,46,48,49,51,52,54,56 and four SRs concluded that the HM in question was not safe (see Supplemental Tables S1 and S2). 33,34,37,…”
Section: Methodsmentioning
confidence: 99%
“…Forty-two SRs failed to mention conflict of interest of the authors. [13][14][15][16][17][18]22,23,[25][26][27][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] Thirty-two SRs made no mention of any source of funding. [13][14][15][16][17]22,23,27,30,[34]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In India, it is commonly consumed as a condiment. It is used in indigestion, arthritis, spondylosis, baldness, diabetes mellitus, and hyperlipidemia [3][4][5][6]. It is also used as appetizer and galactogogues [2,7].…”
Section: Introductionmentioning
confidence: 99%